KAJIAN ETIKA ISLAM - Sain Hanafi (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
Moral awareness is a sense of self that feels good and bad, which is able to distinguish halal and haram, and rights and vanity. Man understands with his deeds. The human being as the subject realizes that he is dealing with his deed now, before, during and after the work is done. This article aims to expose ethics in Islam that is described in ethics towards God, man, and the natural environment. Ethics of God is based on moral law through gratitude to Him. Unlike ethics to man, the nature of his freedom becomes a moral creature that always interact to achieve happiness as the ultimate goal of ethics. In ethics on the environment, attitudes, actions, and ethical perspectives and management of environmental stewardship and all members of the ecosystem are indispensable.